Theoretical Bases of Forming Innovative Regional Development Strategies in the Sphere of Recreation and Tourism - Dmitriy Yurevich Desyatnichenko; Olesya Yurevna Desyatnichenko (Управленческое консультирование)
The article substantiates the need for a strategic approach to the management of the development of tourism and recreation on federal regional levels. The authors examine methodological issues of development of the regional development strategy of tourism and recreational sector, its role and importance in achieving sustainable development of the regional economic system. The authors emphasize the need to use the principles of indicative planning, which allows to link the list of planned quantified indicators with the necessary resources and responsible executives, as well as the time frame to achieve them, leaving thus from declarative and lengthy formulation of priorities, allowing to report on their face but not real achievement, at the same time using the real financial, material and time resources. The article also focused on a number of fundamentally important groups of problems which hinder the development of recreation and tourism, the solution of which requires the use of possibilities and mechanisms of the strategic approach in the management of regional development, studied characteristics and specific features of tourist and recreational zone, conclusion about the need for a strategic approach to planning the development of tourism and recreation that could directly or indirectly have a significant positive impact on the economy of the region, to promote sustainability and innovative nature of its economic development.